A Very Short Introduction to Quantum Field Theory - Stetz, W.A (2007)
Contents: Introduction; Second Quantization and Relativistic Fields; The Interaction Picture and the S-Matrix; The Trouble with Loops; Cross Sections and Decay Rates; The Dirac Equation; The Photon Field; Quantum Electrodynamics.